Epidemic fiction and its representations: from ‘Iliad’ to the novel ‘The plague’, by Camus - Botoso, Altamir (2021)
The epidemic theme is recurrent in Western literature, encompassing books that were written from antiquity to contemporary times. Based on this assumption, the objective of this article is to provide an overview of texts that address this issue and to study the representation of the epidemic outbreak that builds up the novel ‘The plague’, by the french writer Albert Camus, and it is structured based on the convergence of the stories of the adventures of Dr. Bernard Rieux, with personal stories of the following characters: Jean Tarrou, Joseph Grand, Raymond Rambert, priest Paneloux, judge Othon and the mercenary Cottard. The theoretical support for the analyzes is based on the texts by Araújo (2020), Benevides (2011), Develey (2020), Fritsch (2018), Martins (2011), Candido (2011), Marx (2020), Palud (2008), Pereira (1996), Phélip (2020), Ruffato (2020), Voisine-Jechova (2001). Drawing on the intertwining of the stories of various characters, the camusian book unveils the best and the worst in their actions, during an outbreak of bubonic plague in the city of Oran, and presents a sensitive and humanized narrative of the lives of its inhabitants immersed in a period of horror and suffering, marked by tragedy and the pain of family losses, exile and confinement at the borders of a space that is invaded by the disease, which persists over several months, and victimizes a large part of its population